Students' Mathematical Reasoning Ability Viewed from Self-Regulated Learning in the Missouri Mathematics Project Learning with Open-Ended Approach (Unnes Journal of Mathematics Education, 2023)
The mathematical reasoning ability of class VIII students of SMP Negeri 1 Kedungwuni is still relatively low. The purpose of this study is to analyze and describe students' mathematical reasoning abilities in the MMP learning model with an open-ended approach in terms of students' self-regulated learning. The method used is a mixed method with an explanatory sequential design strategy. The results showed that: (1) students' mathematical reasoning abilities in the MMP learning model with an open-ended approach achieved classical mastery; (2) there is a positive influence of students' self-regulated learning on students' mathematical reasoning abilities in the MMP learning model with an open-ended approach, namely 17.1%; (3) the average mathematical reasoning ability of students in the MMP learning model with an open-ended approach is better than the average mathematical reasoning ability of students in learning with a scientific approach; (4) there are differences in students' mathematical reasoning abilities in terms of students' self-regulated learning in the MMP learning model with an open-ended approach; (5) a description of students' mathematical reasoning abilities in terms of self-regulated learning in the MMP learning model with an open-ended approach, namely (a) students with high levels of self-regulated learning are able to fulfill all indicators of mathematical reasoning abilities well; (b) students with intermediate level self-regulated learning tend to be quite capable in all indicators of mathematical reasoning ability; (c) students with a low level of self-regulated learning tend to be able to present mathematical statements, but tend not to be able to fulfill the other three stages.